Waqf Asset Development through the Six Capitals and Sharia Principles: A Muhammadiyah Case Study - Kusumawardani, Diyah Hesti; Suma, Muhammad Amin; Rini, Rini (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2025)
Waqf development faces substantial challenges, primarily due to limitations in financial capital. However, deficiencies in other forms of capital, including manufactured, human, intellectual, social, and natural capital, also impede progress. This study examines these issues through the dual lens of sharia compliance and sustainable finance assessment. Employing a qualitative case study approach, the research draws on primary data collected from a Focus Group Discussion (FGD) with six members of the Muhammadiyah Central Board (2015–2020), analyzed using NVivo software. Findings indicate that while Muhammadiyah demonstrates substantial social and human capital. However, there is a need to enhance environmental infrastructure, strengthen intellectual resources, and develop more effective financial strategies. These include establishing a dedicated waqf investment institution and formalizing the legal status of waqf assets. Holistic capital development is crucial to achieving effective and sharia-compliant waqf asset management. Keyword: sustainable waqf; organizational sustainability; six capitals; Islamic sustainable finance Abstrak. Pengembangan wakaf menghadapi tantangan besar akibat keterbatasan modal, terutama modal finansial. Namun, kekurangan dalam bentuk modal lainnya—seperti modal fisik, manusia, intelektual, sosial, dan alam—juga menghambat kemajuan. Permasalahan ini dianalisis melalui penilaian kepatuhan syariah dan keuangan berkelanjutan. Penelitian ini menggunakan pendekatan studi kasus kualitatif, dengan data primer yang diperoleh dari FGD bersama enam anggota Pimpinan Pusat Muhammadiyah periode 2015–2020, dan dianalisis menggunakan perangkat lunak NVivo. Muhammadiyah menunjukkan modal sosial dan manusia yang kuat, tetapi perlu meningkatkan fasilitas ramah lingkungan, modal intelektual, serta strategi keuangan, termasuk pembentukan lembaga investasi wakaf dan legalisasi aset wakaf. Pengembangan modal secara menyeluruh sangat penting untuk pengelolaan wakaf yang efektif dan sesuai syariah. Kata kunci: wakaf berkelanjutan; keberlanjutan organisasi; enam modal; keuangan Islam berkelanjutan